2007
DOI: 10.1016/j.joca.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium and iodine deficiency on bone, cartilage growth plate and chondrocyte differentiation in two generations of rats

Abstract: Combined selenium and iodine deficiency impaired the growth of bone and cartilage. The changes in the expression of ColX and PTHrP induced by combined selenium and iodine deficiency were compatible to measurements of ColX and PTHrP in Kashin-Beck osteoarthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 17 publications
4
66
1
Order By: Relevance
“…Previous studies have shown that Se deficiency impaired the growth of bone and cartilage [Ren et al, 2007], which has a close relationship with the occurrence of osteoarthritis. In this study, there was higher content of aggrecan and type II collagen in the toxin + Se groups when compared with the toxin groups, suggesting a proanabolic or anticatabolic effect of Se on the ECM component.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that Se deficiency impaired the growth of bone and cartilage [Ren et al, 2007], which has a close relationship with the occurrence of osteoarthritis. In this study, there was higher content of aggrecan and type II collagen in the toxin + Se groups when compared with the toxin groups, suggesting a proanabolic or anticatabolic effect of Se on the ECM component.…”
Section: Discussionmentioning
confidence: 95%
“…High mycotoxin content in cereals has been implicated. 47 Additionally, iodine deficiency combined with selenium deficiency have also been suggested. 47 For instance, rats fed a diet with the mycotoxin T2 developed minor signs of cartilage pathology.…”
Section: Selenium and Cartilagementioning
confidence: 99%
“…The hormone thyroxine also plays an important role in the regulation of bone growth and chondrocyte differentiation (Ren et al, 2007). Although plasma thyroxine concentrations were not significantly lower in the iodine-deficient freshwater reference colony and the iodine-sufficient marine colony, concentrations in gulls from lakes Erie, Ontario, and Huron and the Detroit River were markedly lower than those from both the reference colonies (Fox et al, 2007b).…”
Section: Locationmentioning
confidence: 95%